Observation of compositional domains within individual copper indium sulfide quantum dots. Issue 36 (28th July 2016) - Harvie, Andrew J.; Booth, Matthew; Chantry, Ruth L.; Hondow, Nicole; Kepaptsoglou, Demie M.; Ramasse, Quentin M.; Evans, Stephen D.; Critchley, Kevin
Abstract : We report observation of highly-segregated compositional domains within CuInS2 quantum dots, showing the origin of their emission-mediating InCu defect. Abstract : The origin of photoluminescence in copper indium sulfide (CIS) quantum dots (Qdots) has previously been ascribed to a donor–acceptor pair (DAP) recombination, with a crystal lattice defect implicated as the origin of the donor state. In this study, electron energy-loss spectroscopy (EELS) was used to observe defect-rich compositional domains within individual CIS Qdots, supporting a model of defect-state-mediated photoluminescence for these particles, and identifying them as an ideal model system for future study of lattice defects on Qdot properties.